Empowering the Association of Indonesian National Private Defense Industries (Pinhantanas) to Build the Independence of the Defense Industry - Wulan Nurfitriani; Vicky Nugroho; G. Royke Deksino (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
The fact that the empowerment of the private defense industry needs to be improved. This is indicated by the problems that still exist in the defense industry, namely the lack of government commitment to increasing collaboration between  State-Owned Strategic Industry Enterprises and Private-Owned Enterprises, and many domestic defense industry products that are still imported. This also raises the question, has the private defense industry not fulfilled the local market opportunity? Has the private defense industry yet to fulfill the Domestic Component Level (TKDN) obligation in producing the defense systems? Has the private defense industry yet to cooperate with the foreign defense industry? A literature study method underpins this research, offering the researchers a profound understanding of the Association of Indonesian National Private Defense Industries (Pinhantanas) empowerment. Employing this methodology, insights into defense industry challenges and the Association of Indonesian National Private Defense Industries are revealed. Hence, an investigation into Empowering the Association of Indonesian National Private Defense Industries to Augment Defense Industry Independence proves pivotal. By dissecting defense industry challenges using three research questions, this research offers insights and recommendations to empower the Association of Indonesian National Private Defense Industries (Pinhantanas).